Envelope Detector Development for BFSK signals in PIC18f4550 - Karel Toledo de la Garza; Jorge Torres Gómez (Revista Cubana de Ingeniería, 2013)
This paper concerns demodulator-based Envelope Detector for recovery information in BFSK (Binary Frequency Shift Keying) signal applied upon applications where time symbol synchronization is unknown. Its structure is characterized by 4 filters which are considered in the present article by FIR (Finite Impulse Response), these are unconditionally stables and are always implemented by the same generic difference equation. Towards validating the demodulator, the system is implemented on a Microchip PIC18F4550 interfaced to the PC through USB port, besides in order to manage the system’s operation, it is developed a Matlab application on PC that includes modulation frequency estimation by Fast Fourier Transform method, as well as sending and receiving the modulated and demodulated signals. The convolution between the input samples and the filter coefficients is made in the microcontroller by relying on two tables stored in memory which